Forearm segmental bone defect: Successful management using the Masquelet Technique with the aid of 3D printing technology. (December 2021) - Pachera, Giulia; Santolini, Emmanuele; Galuppi, Alessandra; Dapelo, Emanuela; Demontis, Giacomo; Formica, Matteo; Santolini, Federico; Briano, Stefania
Abstract: The management of forearm nonunion is challenging for orthopaedic surgeons because the forearm is a unique anatomical segment in which all the bones and structures involved embody a complex functional unit. Therefore, when treating such a complex condition, the surgeon must focus not only on bone healing but also on the restoration of the native anatomy in order to replicate the normal relationship between the bones and all the surrounding structures and thus the full function of the forearm, the elbow and the wrist. Here we report the case of a 53-year-old patient with a left forearm deformity due to an atrophic nonunion of the ulna and a malunion of the radius, which was successfully managed with the use of the Masquelet technique associated with a corrective osteotomy of the radius, performed with the aid of a 3D model.